New center of excellence in potato and sweetpotato research - Karnataka, India. Project profile. - International Potato Center (International Potato Center, 2019)
Potato productivity in Karnataka is below the average in India, yet demand is likely to rise. A new center of research excellence will enable the state to benefit fully from potato and sweetpotato intensification.